Techno-economic assessment of various hydrogen production methods – A review - Yukesh Kannah, R.; Kavitha, S.; Preethi; Parthiba Karthikeyan, O.; Kumar, Gopalakrishnan; Dai-Viet, N. Vo; Rajesh Banu, J. (Bioresource technology, 2021)
[Display omitted] •Hydrogen has the potential to unlock 18% of global energy demand in 2050.•96% of H2 is produced from non-renewables and remaining 4% by water electrolysis.•In biomass gasification, feedstock cost demands 20 to 40% of H2 production cost. Hydrogen is a clean fuel that could provide energy incentives and reduce environmental impacts, if production platform is carefully selected and optimized. In specific, techno-economic and sensitivity analysis of the existing hydrogen production platforms and processes is need for an hour to boost the future hydrogen economical aspects. This will have greater impact on future hydrogen production project designs and developing new approaches to reduce the overall production costs to make it as cheaper fuel. The sensitivity analysis of various hydrogen production process such as pyrolysis, gasification, steam reforming of natural gas, dark fermentation, photobiolysis, water electrolysis and renewable liquid reforming were reviewed to evaluate their merits and demerits along with cost-effectiveness. On economic view point, steam reforming of natural gas is efficient, low cost and best methods for hydrogen production. A future research is required to reduce energy input and trapping carbon dioxide emission using membrane models.